“The New Season of Chinese Economic Miracle” and its Challenges - SARMIZA PENCEA (Global Economic Observer)
The investment and export-driven economic model followed by Chinese governments after 1978 served very well their catching-up vision, but China’s unprecedented race to the top had its flaws and drawbacks, leading to negative externalities and multiple structural imbalances. The global economic crisis and the interventionist package implemented to countervail its impact triggered a host of unwanted, negative outcomes which further aggravated the imbalances of the Chinese economy and created some new ones. It therefore became more obvious than ever that the old economic model had reached its limits and it needed to be changed. This task rests with the new cabinet led by premier Li Keqiang who launched a blueprint of bold reforms, but their implementation will presumably meet the strong opposition of powerful vested interests. The paper looks at the structural imbalances of the Chinese economy, highlighting the needed rebalancing processes. It also looks at the reform blueprint designed by the new leadership, disclosing and discussing some of its main implementation challenges.